Perilaku Konsumen dan Mobile Marketing on Pembelian Pakaian Fashion di Shopee - Yeni Yeni; Zakaria Wahap (Penerbit Goodwood, 2024)
Purpose: This study examines the influence of consumer behavior, mobile marketing, and digitalization on product purchasing decisions. The results of this study indicate that consumer behavior is important in influencing product needs. While mobile marketing is a major strategy in modern marketing, with a personalization and accessibility approach, this goal is achieved. Methodology: This study uses a quantitative method, with data collected through questionnaires distributed to respondents who actively use digital platforms in the product purchasing process. Data were collected from 30 students at the Faculty of Economics, Universitas Indo Global Mandiri. Results: The findings demonstrate the importance of innovation in digital marketing strategies to improve consumer experience and product competitiveness in the market. Conclusions: Mobile marketing, and digitalization have a significant impact on purchasing decisions. Consumer behavior is influenced by motivation, attitudes, and social factors. Mobile marketing facilitates access and personalization, while digitalization accelerates decision-making with ease of information and transactions. These three factors improve the shopping experience, conversion, and customer loyalty. Limitations: The results of the study indicate that consumer behavior and mobile marketing significantly influence purchasing decisions, while product digitalization acts as a mediator that strengthens this relationship. Contribution: Consumer behavior, mobile marketing, and digitization influence product-purchasing decisions. This study provides new insights into the importance of consumer behavior driven by digital factors and mobile marketing in determining purchasing decisions.